Comparative Study of Quality Changes in Shea Butter Coated Pawpaw Carica papaya Fruit During Storage - Adetuyi, F.O.; Ayileye, T.A.; Dada, I.B.O. (Pakistan Journal of Nutrition, 2008)
The storage of shea butter coated pawpaw carica papaya fruit at different storage temperature was investigated as regard the nutrients, sugars and minerals. Freshly harvested just ripe fruit of pawpaw carica papaya was coated with shea butter and stored at room temperature (27°C ± 1°C), refrigeration temperature (10°C ± 1°C)and freezing temperature (-5°C ± 1°C) for 8 days. The proximate, sugar (glucose, fructose and galactose) and minerals (Ca, Mg, Fe and Zn) were subsequently determined. The result of the study shows that the moisture content increases significantly (P≤0.05) (85.25-95.25%) while other nutrients reduce significantly (P≤0.05) in storage, the sugar and the minerals content also reduce significantly (P≤0.05) in storage. The storage temperature of freezing temperature recorded the highest mineral content (Ca-113.33mg/100g, Mg- 53.33mg/100g, Fe- 2.33mg/100g and Zn- 7.00mg/100g) at the end of the storage period which was significantly (P≤0.05) higher than other storage temperatures. At the end of the storage period, there was no significant difference (P≤0.05) in the glucose and fructose content of the pawpaw at the different storage temperatures.